Exploring the Acceptance of Online Classes in Nepal: Application of Technology Acceptance Model - Subedi, Mohan (Rupantaran: A Multidisciplinary Journal, 2020)
The paper aims to explore the acceptance of online classes in Nepal using Technology acceptance model. TAM is the most widely used model to examine the acceptance of technology by users. The results have been obtained from self-administered questionnaire from different users of online class. The responses received were analyzed by several statistical tools namely Frequency distribution, Cronbach’s Alpha Reliability rest, Pearson Correlation coefficient and Multiple regression computed by SPSS version 26. The main conclusion drawn from this study is that perceived usefulness has much impact on intention to use online classes. Perceived usefulness and perceived ease to use have significant relationship with intention to use online classes.